2013
DOI: 10.4236/jep.2013.49105
|View full text |Cite
|
Sign up to set email alerts
|

Medical Waste Management: A Case Study of the Souss-Massa-Drâa Region, Morocco

Abstract: Medical waste management is of major concern due to the potentially high risks to both human health and the environment caused by inadequate waste management practices. In Morocco, as in many developing countries, little information is available regarding generation handling, and disposal of medical waste. The specific objective of this study was to analyse the medical waste management practices in the Souss-Massa-Drâa region, Morocco. The study was carried out in seven of the twelve hospitals in the region, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…The findings in this study corroborate some rates recorded in Souss-Massa-Draa, where an average rate of 0.53 kg/bed/day was recorded [1]. Furthermore, a study carried out in 2008 by Abdulla et al, showed that waste weighted average was 0.83 kg/bed/day in northern Jordan and 1.22 kg/bed/day was reported by Ruoyan et al, in 2010 as weighted average rate in Binzhou Distrinct in China [27, 28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings in this study corroborate some rates recorded in Souss-Massa-Draa, where an average rate of 0.53 kg/bed/day was recorded [1]. Furthermore, a study carried out in 2008 by Abdulla et al, showed that waste weighted average was 0.83 kg/bed/day in northern Jordan and 1.22 kg/bed/day was reported by Ruoyan et al, in 2010 as weighted average rate in Binzhou Distrinct in China [27, 28].…”
Section: Discussionsupporting
confidence: 91%
“…Waste generation source, categorization, quantity and quality are the key issues to decide an effective medical waste management practice [1]. The medical staff in the surveyed hospitals had adequate knowledge of the various categories of the wastes generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oh and Lee [44] applied the Meta-frontier method to the global reference M index and decomposed Meta-M. Following existing studies, the decomposition process of the META-GML used in this study is shown in formula (5): (5) where, EC refers to the change of technical efficiency TE within each group from period t to period t+1; BPG (Best Practice Gap) refers to the gap between the current frontier of each group and the global frontier of each group ① ; BPC (Best Practice Change)…”
Section: Meta-frontier-global-malmquist-luenberger Indexmentioning
confidence: 99%
“…Mbarki et al [22] analysed clinical waste management practices in Morocco. The results of their survey on the separation of medical waste revealed that the knowledge of the staff on waste segregation was low.…”
Section: Current Status Of Clinical Waste Segregation and Relatedmentioning
confidence: 99%